First listen and post-graduate training: a setting to develop a psychological professional approach. - Impagliazzo, Francesco (Rivista di Psicologia Clinica, 2013)
The report focuses on the contribution of the trainee psychologist in building a setting of first listen in the context of a psychological territorial service. Through the exploration of their own emotions into institutional and dual context and relating them to the consultant emotions as a part of the knowledge interview, the trainees activate a thinking process and thus develop their professional approaches. This can benefit the relationship between services and users.